2017
DOI: 10.1186/s12891-017-1651-9
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of porously punched prosthetic short stem virtually designed for simulative uncemented Hip Arthroplasty

Abstract: BackgroundThere is no universal hip implant suitably fills all femoral types, whether prostheses of porous short-stem suitable for Hip Arthroplasty is to be measured scientifically.MethodsTen specimens of femurs scanned by CT were input onto Mimics to rebuild 3D models; their *stl format dataset were imported into Geomagic-Studio for simulative osteotomy; the generated *.igs dataset were interacted by UG to fit solid models; the prosthesis were obtained by the same way from patients, and bored by punching bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…4 a). The results were similar to that of comparable studies [ 24 , 25 ], which demonstrated the reliability of the finite element model.
Fig.
…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…4 a). The results were similar to that of comparable studies [ 24 , 25 ], which demonstrated the reliability of the finite element model.
Fig.
…”
Section: Resultssupporting
confidence: 89%
“…The Fig. 3 The prosthesis migration evaluation: the stem tip migration was calculated as [(a-A) + (B-b)]/2 results were similar to that of comparable studies [24,25], which demonstrated the reliability of the finite element model.…”
Section: The Stress and Displacement Of The Normal Femursupporting
confidence: 72%
See 1 more Smart Citation
“…With the progress of socialization in China, the aging of population has been increasingly prominent. The elderly population is often accompanied with various medical diseases, especially in middle-aged women who are often accompanied with osteoporosis, so the slight trauma can lead to femoral intertrochanteric fracture easily ( 1 ). Intertrochanteric fractures in senile patients are mostly unstable fractures accompanied with osteoporosis, while the fractures are often comminuted, involving the large and small intertrochanteric fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Joint replacement is a prevalent approach to achieve function restoration of degenerative joint diseases [1]. Therefore, the analysis of the mechanical properties of the femur is of great significance in the design and manufacture of the implantable prosthesis [2].…”
Section: Introductionmentioning
confidence: 99%